The school in the Quechua peasant world: sociocultural tensions between modes of socialization of knowledge - Zambrana Vargas, Jaime (Education Policy Analysis Archives, 2006)
The implementation of State educational reforms has sidestepped the reality of a heterogeneous society and Bolivia?s cultural diversity. The pedagogic models of formal schooling have been thrust upon a rural world and fail to respond to the needs and socio-cultural interests of an indigenous peasant youth. As a result, the institutionalized school?an instrument geared toward homogenizing the culture?has failed to be sensitive to diverse indigenous cosmic visions, which has historically and repeatedly resulted in cultural conflicts, bargaining and mediation. This study takes a socio-historical perspective to qualitatively analyze the tensions between the modes of socialization of knowledge?formal schooling vs. peasant community?in the transformative processes of the State education system. From the perceptions and interactions of the educational social actors, the modes of socialization?as cultural and pedagogical phenomena?reveal a complexity of manifestations regarding meaning/significance from the distinct cosmic visions of the different actors. The study reveals and contrasts the characteristics and inter-relationships of the different visions and discourses in the forms of socialization between formal schooling and the peasant community in the context of implementing State educational reform at the municipal level.